EXPLORING UNDERGRADUATE STUDENTS’ PERCEIVED BENEFITS OF USING TIKTOK FOR ENGLISH LISTENING PRACTICE - Prameswari, Ajeng (Journal of English Education and Linguistics, 2026)
Abstract TikTok has become one of the most widely used digital platforms among university students, offering potential benefits for English listening practice. However, little is known about how learners personally experience using TikTok specifically for listening, particularly regarding the types of linguistic input they learn, the patterns and trends that support comprehension, and the strategies they use to manage listening difficulties. This study employed a qualitative phenomenological design involving semi-structured interviews with three English Education students. Thematic analysis revealed two major themes: (1) TikTok provides authentic, enjoyable, and motivating listening experiences through exposure to informal expressions, reduced forms, and predictable content patterns such as story time and commentary videos; and (2) students apply self-directed strategies such as replaying videos, using captions, and selecting content aligned with their proficiency. An integrative meaning showed that students perceive TikTok as a space where entertainment and learning naturally intersect. These findings suggest that TikTok can serve as a flexible supplementary tool for developing English listening skills.